Kewenangan Pemerintah Daerah Pasca Pencabutan Kebijakan Ppkm Terhadap Kesadaran Kesehatan Masyarakat Di Kota Tangerang - handayani, fitri; Fasyehhudin, Muhammad; Rayhan, Ahmad (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The Covid-19 pandemic has changed the global perspective on health, including in Indonesia. The authority of the government has become crucial in responding to this health crisis. Various policies were implemented to protect the public and minimize the negative impact on public health. This study aims to understand the authority and efforts of the local government after the lifting of the PPKM (Public Activity Restrictions) policy on public health awareness in Tangerang City and to identify the obstacles faced by the Tangerang City Government after the lifting of the PPKM policy concerning public health awareness in Tangerang City. This research uses an empirical juridical method with a descriptive-analytical specification, and data were obtained through in-depth interviews with sources. The research findings identify that after the PPKM policy was lifted, the Tangerang City Government did not issue new policies to follow up on the previous one. The conclusion of this study is that the Tangerang City Government continues to implement health efforts such as health protocols, surveillance, vaccination, and public communication to address the aftermath of the PPKM policy lift. The inhibiting factor post-PPKM policy lift, according to the Tangerang City Government, is the absence of any significant obstacles. This is due to the return to the public's own health awareness.